DYNAMICS OF Sardinella lemuru IN THE BALI STRAIT: ANALYSIS OF FLUCTUATIONS AND SUSTAINABILITY FROM 2014 TO 2024 - Seruni Ajeng Amiati; I Nyoman Suyasa; Meuthia Aula Jabbar; Widodo Setiyo Pranowo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
Sardinella lemuru was an important fishery commodity in the Bali Strait, with significant production fluctuations. This study aims to analyze the production dynamics of Sardinella lemuru for the period 2014–2024 and identify the factors influencing them. The research method employed quantitative descriptive analysis and temporal trend analysis of production data from the Pengambengan Fisheries Research Station (PPN) and the Muncar Fisheries Research Station (PPP). The results indicate that Sardinella lemuru production is highly fluctuating, exhibiting a cyclical pattern every 2–3 years. The 2017–2018 period was the lowest in the past 11 years, with production not exceeding 300 tons per month. This collapse was influenced by overfishing during the 2014–2017 period, as evidenced by the declining CPUE trend. Other factors affecting production fluctuations include the biological cycle of Sardinella lemuru, seasonal migration patterns, and changes in oceanographic conditions. A significant increase in production began in 2020–2024, indicating a recovery of stock following the collapse period. This study suggests the need for sustainable management through the implementation of a quota system and improved gear selectivity.